A perturbative approach to complexity during shearing, dissipative collapse - Kevin Reddy; Megan Govender (European Physical Journal C: Particles and Fields)
Abstract We investigate the notion of complexity as defined by Herrera et al. (Phys Rev D 97:044010, 2018) for a star undergoing dissipative collapse in the presence of shear. We adopt a perturbative scheme which tracks the onset of collapse from an initially static configuration described by the Bowers–Liang model. The complexity for the initially static configuration is driven solely by the anisotropy and grows as the difference in the radial and tangential stresses grow. As the star loses equilibrium and transits into a dissipative collapse phase, the dynamical complexity is enhanced by contributions from the anisotropy and density inhomogeneity. The novelty of our work highlights the impact of pressure anisotropy and density inhomogeneity to the evolution of the complexity factor as a self-gravitating body evolves from an initially complexity-free and static regime into a dynamical radiating stellar object in the presence of shear.